Biotic and abiotic treatments as a bet‐hedging approach to restoring plant communities and soil functions. Issue 2 (7th September 2021) - Rader, Audrey J.; Chiquoine, Lindsay P.; Weigand, James F.; Perkins, Judy L.; Munson, Seth M.; Abella, Scott R.
Abstract : Two related concepts in restoration ecology include the relative interchangeability of biotic and abiotic restoration treatments for initiating recovery and bet hedging using multiple restoration approaches to increase the likelihood of favorable restoration outcomes. We used these concepts as a framework to implement a factorial experiment including biotic (outplanting greenhouse‐grown individuals of three perennial species) and abiotic treatments (constructing microtopography or vertical mulch consisting of upright, dead plant material). These treatments were designed to stimulate native plant recruitment and reverse soil degradation at four disturbed sites in the Sonoran Desert, U.S.A. The first growing season after the restoration treatments was the driest of the last 47 years, and 100% of outplants died. While the biotic treatment failed, the vertical mulch abiotic treatment increased native shrub seedling cover at the driest site and reversed soil loss across sites by increasing soil accumulation by 6× to 2 cm/year. Results revealed that (1) inexpensive, minimal‐input abiotic treatments outperformed resource‐intensive biotic treatments; (2) the restoration effort withstood the total failure of a major component (outplanting) to nevertheless achieve key restoration benefits within 2–3 growing seasons; and (3) incorporating multiple treatment types served as a bet‐hedging approach to buffer against treatment failures. Integrating minimal‐input abiotic treatments in restoration warrants consideration given their low cost and bet‐hedging potential.